2015
DOI: 10.3390/su70912958
|View full text |Cite
|
Sign up to set email alerts
|

Risk Assessment of Regional Irrigation Water Demand and Supply in an Arid Inland River Basin of Northwestern China

Abstract: Irrigation water demand accounts for more than 95% of the total water use in the Kaidu-kongqi River Basin. Determination of the spatial and temporal trends in irrigation water demand is important for making sustainable and wise water management strategies in this highly water deficit region. In this study, the spatial and temporal trends in irrigation water demand as well as net crop irrigation water requirements for nine major crops during 1985-2009 were analyzed by combining the Penman-Monteith equation reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 16 publications
2
11
0
Order By: Relevance
“…The peak of the groundwater level is opposite to the seasonal variation in precipitation ( Figure 3c); therefore, this peak appears in March, whereas the minimum value appears in August (Figure 5b). This finding is most likely caused by the seasonal extraction of groundwater for irrigation [63][64][65]. Figure 5c shows the monthly GWSA estimated by multiplying GWSA with the average specific yield.…”
Section: Lu/lc Class Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…The peak of the groundwater level is opposite to the seasonal variation in precipitation ( Figure 3c); therefore, this peak appears in March, whereas the minimum value appears in August (Figure 5b). This finding is most likely caused by the seasonal extraction of groundwater for irrigation [63][64][65]. Figure 5c shows the monthly GWSA estimated by multiplying GWSA with the average specific yield.…”
Section: Lu/lc Class Descriptionmentioning
confidence: 99%
“…10 of 18 appears in August (Figure 5b). This finding is most likely caused by the seasonal extraction of groundwater for irrigation [63][64][65]. Figure 5c shows the monthly GWSA estimated by multiplying GWSA with the average specific yield.…”
Section: Gws Changesmentioning
confidence: 99%
“…However, there are some possibilities to make a comparison. Guo et al (2015) found that the mean net irrigation requirement in the Kaidukongqi river basin in China reached 861 mm between 1985 -2009 years. Rodrigues et al (2003) reported that the average value of the NIR was 826 mm.…”
Section: Resultsmentioning
confidence: 99%
“…Estimation of crop water requirement on different crops and locations have also been reported in several previous studies. (Tan, 2018;Guo et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The WFs of crops can provide an important guidance for the adjustment of agricultural structure in water scarce areas. Some other influential factors should also be considered in deciding the planting structures besides water factor, like planting conditions, farmers' habits, cultural and climatic change [60][61][62]. Therefore, the above suggestions from the perspective of the water footprint strategy may be limited.…”
Section: Discussionmentioning
confidence: 99%